APORTES A LA BIOLOGÍA DEL ESCARABAJO SUDAMERICANO SULCOPHANAEUS LEANDER (WATERHOUSE, 1891) (COLEOPTERA: SCARABAEIDAE) - Noriega Alvarado, Jorge Ari (Instituto de Ecología, A.C., 2002)
In a zone of tropical rain forest of the Colombian amazonic region a study on the south american beetle Sulcophaneus leander was carried out, using pitfall sampling methods and ad libitum observations of the captured specimens. The beetle presents strictly coprophagic feeding habits and its presence is restricted to river beaches, being the only species found there in abundance; it uses dung from different animals (mammals and reptiles) and its flight activity shows two peaks along the day: one at dawn and one at dusk. The sand and dung remotion activity was visible through the night, early in the morning and the late evening. The construction of poorly curved alimentary galleries was observed below the excrement samples, reaching an approximate length of half a meter. The present study gives some information of the geographical distribution of this species, based on collections from different localities.